Pengolahan Sludge IPAL Industri Kue dan Makanan Ringan dengan Metode Composting - Alessandra Nancy Wattimena; Syadzadhiya Qothrunada Zakiyayasin Nisa (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Waste sludge is sludge that contains a lot of solids resulting from solid-liquid separation from industrial waste. The waste sludge produced from the waste processing process will create new problems in handling because it can pollute the environment. This research will discuss the use of IPAL sludge originating from the Sludge Drying Bed (SDB) to be used as organic fertilizer. In the process of making organic fertilizer in the cake and snack industry by monitoring parameters such as color, texture, smell and properties of organic fertilizer during the process of making organic fertilizer. The characteristic results obtained in this research are blackish brown color, rough texture, earthy odor and the resulting moisture is dry. Thus, the use of WWTP sludge as organic fertilizer offers an innovative and industrial solution that contributes positively to the environment.